New Evidenceon Cyclical and Structural Sources of Unemployment - Chen, Jinzhu (IMF Working Papers; Working Paper ;, 2011)
We provide cross-country evidence on the relative importance of cyclical and structural factors in explaining unemployment, including the sharp rise in U.S. long-term unemployment during the Great Recession of 2007-09. About 75% of the forecast error variance of unemployment is accounted for by cyclical factors-real GDP changes (?Okun's Law?), monetary and fiscal policies, and the uncertainty effects emphasized by Bloom (2009). Structural factors, which we measure using the dispersion of industry-level stock returns, account for the remaining 25 percent. For U.S. long-term unemployment the split between cyclical and structural factors is closer to 60-40, including during the Great Recession.